Mathematical Models of Papermaking - Buikis, A.; Cepitis, J.; Kalis, H.; Reinfelds, A.; Ancitis, A.; Salminš, A. (Nonlinear Analysis: Modelling and Control, 2001)
The mathematical model of wood drying based on detailed transport phenomena considering both heat and moisture transfer have been offered in article. The adjustment of this model to the drying process of papermaking is carried out for the range of moisture content corresponding to the period of drying in which vapour movement and bound water diffusion in the web are possible. By averaging as the desired models are obtained sequence of the initial value problems for systems of two nonlinear first order ordinary differential equations.
Keywords: wood drying; mathematical models; heat and moisture transfers